Avian İnfluenza: The Past and Present Status - AK, Seyyal (Cerrahpaşa Medical Journal, 2014)
Avian influenza one of the most important viral diseases which leds to major economic losses and threatens the poultry industries. On the other hand, zoonotic importance of the disesae and increase in the number of lethal human cases make this infection, that also threatens human health with a risk of new pandemic, a current issue. In this review, current knowledges on, avian influenza were discussed.